Dakwah Islam di Media Digital Sebuah Tinjauan Konseptual - Fasha, Julia; Salama, Hartini; Azzahro, Fatimah (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study aims to explore the concept of da‘wah in the context of digital media, particularly with regard to strategies for delivering da‘wah messages. The study employs a literature review method by examining various relevant scholarly sources to obtain a conceptual description of digital da‘wah. The research follows four main stages: preparation; compilation of topic-related literature as the research bibliography; determination of the research timeline; and discussion of the findings. The results indicate that digital da‘wah comprises several key aspects. First, digital media are characterized by reach and engagement, which must be understood by preachers to ensure effective message delivery. Second, digital da‘wah is interactive and participatory through comment and discussion features provided by social media platforms. Third, the relevance and impact of content play a crucial role in determining the effectiveness of da‘wah. Fourth, da‘wah content contributes to the development of visual identity, message consistency, and the personal branding of the preacher. Fifth, the aspects of production, distribution, and evaluation serve as important indicators for maintaining quality and measuring the performance of digital da‘wah. Ultimately, the effectiveness of digital da‘wah is strongly determined by the values conveyed, scholarly validity, and the exemplary conduct of the preacher in communicating Islamic teaching